The importance of cluster analysis for enhancing clinical practice: an example from irritable bowel syndrome - Sula Windgassen; Rona Moss‐Morris; Kimberley Goldsmith; Trudie Chalder (2018)
In clinical populations, substantial heterogeneity exists in patient characteristics, illness severity and treatment responses. Better understanding of such heterogeneity may lead to more effective...